Improving the labor market outcomes of minorities: the role of employment quota - Nishith Prakash (Institute for the Study of Labor (IZA), 2009)
The world's biggest and arguably most aggressive form of employment based affirmative action policy for minorities exists in India. This paper exploits the institutional features of federally mandated employment quota policy to examine its effect on labor market outcomes of two distinct minority groups. My main finding is that employment quota significantly in- creases the probability of acquiring a salaried job for one minority group and not the other. Their improved employment outcome is also reflected in their higher household consumption expenditure. Overall, the effects vary within each minority group by education, gender, and geographical location.
Keywords: H40; J21; J31; J45; O10; 330; Caste; employment; wage differentials; public sector; India; Arbeitsmarktpolitik; Minderheitenpolitik; Soziale Schicht; Öffentlicher Dienst; Lohndifferenzierung; Wirkungsanalyse; Indien